Export Commodity Production and Broad-Based Rural Development: Coffee and Cocoa in the Dominican Republic - Siegel, Paul B.; Alwang, Jeff (World Bank, Washington, D.C., 2013)
An estimated 80,000-100,000 Dominican farmers produce coffee and cocoa, nearly 40 percent of all agricultural producers. The sectors also provide employment for tens of thousands of field laborers and persons employed in linked economic activities. The majority of coffee and cocoa producers are small-scale and most are located in environmentally sensitive watersheds. Recent trends in international commodity markets have challenged the survival of both sectors. Production is characterized by low yields and uneven quality, while periodic hurricanes have contributed to a lackluster and unstable record of output and exports. Despite these conditions, most experts acknowledge the fact that appropriate agro-ecological conditions exist in Dominican Republic for production of high-quality coffee and cocoa. To be competitive and sustainable, some changes must take place in the coffee and cocoa sectors. The objective of this study is to provide an overview of the coffee and cocoa sectors, to identify major problems, and to suggest possible strategies to deal with these problems. The authors conclude that if the objectives of the government are poverty reduction, environmental protection and overall well-being of rural society, it is critical to move beyond a commodity-specific approach to a broader rural development focus on households, regions and environments where coffee and cocoa are currently being grown.